Bioamperometric Systems with Fructose Dehydrogenase From Gluconobacter japonicus for D‐Tagatose Monitoring. Issue 6 (25th March 2021) - Voitechovič, Edita; Stankevičiūtė, Jonita; Vektarienė, Aušra; Vektaris, Gytis; Jančienė, Regina; Kuisienė, Nomeda; Razumienė, Julija; Meškys, Rolandas
Abstract: D‐Tagatose is a rare natural sugar, which is promising alternative for popular dietary sweeteners. To optimize and make D‐tagatose production more cost‐effective, a portable (bio)sensor would be beneficial for D‐tagatose quantification in bioreactor media during D‐tagatose (bio)synthesis. In this study, a pilot study of D‐tagatose quantification by a bioamperometric system is reported. A key feature of the system is usage of fructose dehydrogenase from Gluconobacter japonicus, widely known as a highly fructose‐specific enzyme, and 2‐arylamino‐1, 4‐benzoquinone derivatives, as electron transfer mediators from the enzyme to carbon electrodes. The system has been validated as biosensor for D‐tagatose quantification in the fermentation medium. Abstract :